Preparation method of zirconium phosphate and zirconium phosphate
By dissolving zirconium dioxide with hydrofluoric acid to form a fluorozirconic acid solution and reacting with phosphoric acid at high temperature, the problems of low yield and low purity in the prior art were solved, and the preparation of zirconium phosphate with high purity and high yield was achieved.
Patent Information
- Application Number
- CN202411599055.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-03-04
AI Technical Summary
In the preparation of zirconium phosphate, the yield is low, the purity is low, and it is easily doped with impurities such as chloride ions or nitrates, which affects the quality of the product.
Hydrofluoric acid is used to dissolve zirconium dioxide to form a fluorozirconic acid solution, and then react with phosphoric acid at a high temperature of 150-180°C to form zirconium phosphate, and the purity and yield of the product are improved by steps such as washing and high-temperature drying.
The high purity and high yield of zirconium phosphate are achieved, the introduction of impurities is avoided, and the quality and preparation efficiency of the product are improved.
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method of zirconium phosphate and zirconium phosphate. Background Art
[0002] Zirconium phosphate has a wide range of uses, mainly as an additive for ceramic materials, coatings, and polymer composite materials. Adding zirconium phosphate to ceramic materials can improve the high temperature resistance, acid and alkali resistance, and scratch resistance of ceramic materials, reduce the thermal expansion of ceramic materials, improve the thermal stability and chemical stability of ceramic materials, and increase the toughness of ceramic materials. Adding zirconium phosphate to coatings can increase the adhesion, leveling, dispersibility, high temperature resistance, and acid and alkali resistance of the coatings. At the same time, it can also remove the harmful odor of the coatings, enhance the friction reduction and wear resistance, and thus extend the service life of the coatings. Adding zirconium phosphate to polymer composites can improve the toughness, tensile strength, and stability of polymer composites.
[0003] A Chinese patent document with application number 200410000629.2 discloses a method for preparing zirconium phosphate, wherein a soluble zirconium salt (zirconium oxychloride, zirconium carbonate or zirconium oxysulfate) is dissolved in water, and then a 40% by mass aqueous solution of hydrofluoric acid and 85% by mass phosphoric acid are added, and then the mixed solution is stirred at 60-90°C for 2-4 hours, filtered after cooling, washed until the pH value of the washing solution is approximately equal to 6, and dried to obtain zirconium phosphate α-Zr(HPO4)·H2O crystals. In this scheme:
[0004] When zirconium oxychloride is used as the soluble zirconium salt, phosphoric acid is not capable of completely replacing the zirconium in zirconium oxychloride both in theory and in practice. The prepared zirconium phosphate will be doped with a large amount of chloride ions, and the purity of the zirconium phosphate cannot be guaranteed. In addition, since the total amount of chloride ions and phosphates in the synthetic liquid is greater than that of zirconium ions, a portion of the zirconium will be dissolved in the synthetic liquid and cannot be recovered. Even if the synthetic liquid is reused, the concentration of chloride ions in the synthetic liquid will become higher and higher, and eventually it cannot be used.
[0005] When zirconium carbonate is used as the soluble zirconium salt, since zirconium carbonate is an intermediate product in the production of zirconium oxide, its main component is a mixture of zirconium carbonate and zirconium oxide, and there is bound water and free water. The ratio of zirconium carbonate to zirconium oxide is difficult to verify, and the water content is also different. As a result, the ratio of phosphoric acid to zirconium carbonate cannot be accurately matched during the synthesis process, and the purity of the product is not stable enough.
[0006] When zirconyl sulfate is used as the soluble zirconium salt, phosphoric acid is a medium-strong acid and sulfuric acid is a strong acid. According to the theory of strong acid to weak acid, phosphoric acid cannot completely replace the sulfate in zirconyl sulfate, resulting in incomplete reaction, too high sulfate impurity content, and low purity of the finally prepared zirconium phosphate.
[0007] In addition, the background technology section of the Chinese patent document with application number 200410000629.2 also discloses the use of an HF method, wherein a soluble zirconium salt (zirconium oxychloride or zirconium nitrate) is dissolved in hydrofluoric acid (HF), phosphoric acid is added, and a product (zirconium phosphate) is obtained under heating and stirring. However, in fact, in the presence of nitrate radicals or chloride ions, the addition of hydrofluoric acid does not conform to the theory of preparing a weak acid with a strong acid, and insoluble crystals cannot be formed in theory. Even if crystallization is forced through a concentration approach, a large amount of soluble chlorides will be mixed, and these soluble chlorides must be removed by washing, which will result in a very low yield of zirconium phosphate. Summary of the invention
[0008] In order to solve the technical problems of low yield and low purity when zirconium phosphate is prepared by the existing method, the present invention provides a method for preparing zirconium phosphate and zirconium phosphate.
[0009] The technical solution of the present invention is:
[0010] A method for preparing zirconium phosphate, which is special in that it comprises the following steps:
[0011] Step 1, preparing a fluorozirconic acid solution;
[0012] Step 1.1: Add zirconium dioxide to hydrofluoric acid with a mass fraction of 40-50% (if the mass fraction is too low, the reaction is too slow and the dissolution is poor; if the mass fraction is too high, the volatilization is too serious and it is difficult to operate) to dissolve, the molar ratio of hydrofluoric acid to zirconium dioxide is 6:1, keep the temperature at 80-100°C (below 80°C, the reaction will be very slow or even no reaction), stir and dissolve until transparent, and obtain a crude fluorozirconic acid solution;
[0013] Step 1.2: filtering the crude fluorozirconic acid solution to obtain a refined fluorozirconic acid solution;
[0014] Step 2, synthesizing zirconium phosphate;
[0015] Step 2.1: heat phosphoric acid with a mass fraction of 60-85% to 150-180° C. (if the temperature is too low, the evaporation rate and reaction rate will be slow, and if the temperature is too high, the safety factor will be reduced during the reaction), and slowly add the fluorozirconic acid solution to it, and the molar ratio of zirconium to phosphorus is 3:4;
[0016] Step 2.2: The solution obtained in step 2.1 is kept warm at 150-180° C. for heating reaction. During the process, pure water / high-purity water is appropriately added to prevent it from being evaporated to dryness. When a large amount of precipitation is produced, the supernatant is taken for mid-control. When the content of hydrofluoric acid in the supernatant is less than 2% (at this time, not only the purity of zirconium phosphate can be guaranteed, but also the yield of zirconium phosphate in the subsequent water washing process can be guaranteed), it indicates that the heating reaction is completed, and the supernatant is removed to obtain a precipitate.
[0017] Step 2.3: Filter the precipitate and wash with water until the F ions in the precipitate are less than 50 ppm, thereby obtaining a crude zirconium phosphate; although most of the fluorine ions will evaporate during the synthesis of zirconium phosphate, they cannot be completely removed, so they need to be washed with water to be removed;
[0018] Step 3, drying;
[0019] The crude zirconium phosphate product is dried at 500-600°C for 2-3 hours, and the drying is completed when the weight loss on ignition at 500°C is less than 0.5%, thereby obtaining a zirconium phosphate product. The obtained zirconium phosphate product is tested, and the phosphorus pentoxide content is 43.5%-44%, and the zirconium oxide content is 56%-56.5%.
[0020] Furthermore, in step 1.2, filtration is performed using a precision filter with a filtration accuracy of 1 micron.
[0021] Furthermore, the mass fraction of phosphoric acid used in step 2.1 is 85%, at which time the time taken for heating reaction and evaporation is short and the preparation efficiency is high.
[0022] The present invention also provides a zirconium phosphate, which is special in that it is prepared by the above method.
[0023] The present invention also provides a ceramic material, which is special in that the above-mentioned zirconium phosphate is added into the ceramic material.
[0024] The present invention also provides a coating, which is special in that the above-mentioned zirconium phosphate is added into the coating.
[0025] The present invention also provides a polymer composite material, which is special in that the above-mentioned zirconium phosphate is added into the polymer composite material.
[0026] The advantages of the present invention are:
[0027] 1. The present invention utilizes the principle of strong acid to produce weak acid, firstly uses hydrofluoric acid to dissolve zirconium dioxide to generate fluorozirconic acid, then uses fluorozirconic acid to react with phosphoric acid to generate zirconium phosphate and hydrofluoric acid, and during the reaction of fluorozirconic acid and phosphoric acid, the temperature is always maintained at 150-180° C., so that most of the hydrofluoric acid generated by the reaction is evaporated, and finally the remaining small amount of hydrofluoric acid is washed away with water. No other ions such as chloride ions and nitrate ions are introduced in the entire preparation process, thereby ensuring the purity of the zirconium phosphate while taking into account the yield.
[0028] 2. When the present invention utilizes fluorozirconic acid and phosphoric acid to react, their molar ratio is strictly fixed within the range of generating zirconium phosphate to ensure that the generated product is zirconium phosphate, which is completely converted into a zirconium phosphate product through subsequent high-temperature drying. DETAILED DESCRIPTION
[0029] The present invention is conceived as follows:
[0030] Zirconium dioxide is very stable in nature. It cannot react fully with acids other than hydrofluoric acid under normal conditions, and cannot react directly with phosphoric acid. Therefore, the present invention uses hydrofluoric acid to dissolve zirconium dioxide first, and then uses the method of strong acid to make weak acid to evaporate the hydrofluoric acid with phosphoric acid, thereby utilizing the characteristic of hydrofluoric acid as a low-boiling acid to volatilize most of the hydrofluoric acid at a higher temperature, and finally the very small amount remaining is washed with water.
[0031] Reaction equation:
[0032] ZrO2+6HF====H2ZrF6+2H2O
[0033] 3H2ZrF6+4H3PO4====Zr3(PO4)4+18HF
[0034] The present invention is further described in detail below by way of examples.
[0035] Example 1
[0036] In this example, zirconium phosphate is prepared by the following steps:
[0037] Step 1, preparing a fluorozirconic acid solution;
[0038] Step 1.1: add 50% hydrofluoric acid by mass into a tetrafluoroethylene beaker, add zirconium dioxide thereto for dissolution, the molar ratio of hydrofluoric acid to zirconium dioxide being 6:1, maintain the temperature at 80°C, stir and dissolve until transparent, and obtain a crude fluorozirconic acid solution;
[0039] Step 1.2: Filter the crude fluorozirconic acid solution using a precision filter with a precision of 1 micron to obtain a fine fluorozirconic acid solution.
[0040] Step 2, synthesizing zirconium phosphate;
[0041] Step 2.1: add 85% phosphoric acid by mass into a tetrafluoro beaker, then place the tetrafluoro beaker containing phosphoric acid into an oil bath, heat to 150°C, and slowly add the fluorozirconic acid solution obtained in step 1.2, wherein the molar ratio of zirconium to phosphorus is 3:4;
[0042] Step 2.2: The solution obtained in step 2.1 is kept at 150°C for further heating reaction and evaporation. As the hydrofluoric acid generated by the reaction is continuously evaporated, a white precipitate begins to appear in the solution. The heating reaction is continued at this temperature. During the process, pure water is appropriately added to prevent the solution from being evaporated to dryness. When a large amount of precipitate is produced, the supernatant is taken and a fluoride ion meter is used for mid-control. When the hydrofluoric acid content in the supernatant is about 0.86%, the heating reaction is considered to be completed, and the supernatant is removed to obtain a precipitate.
[0043] Step 2.3 Filter the precipitate obtained in step 2.2 and wash with water until the F ion is less than 50 ppm to obtain a crude zirconium phosphate.
[0044] Step 3, drying the zirconium phosphate;
[0045] The crude zirconium phosphate obtained in step 2.3 was added to an alumina crucible and dried at 500°C for 3 hours. When the ignition loss at 500°C was less than 0.5%, the drying was completed to obtain a zirconium phosphate product. The obtained zirconium phosphate product was tested, and the phosphorus pentoxide content was 43.5% and the zirconium oxide content was 56.1%.
[0046] Example 2
[0047] In this example, zirconium phosphate is prepared by the following steps:
[0048] Step 1, preparing a fluorozirconic acid solution;
[0049] Step 1.1: add 40% hydrofluoric acid by mass into a tetrafluoroethylene beaker, add zirconium dioxide thereto for dissolution, the molar ratio of hydrofluoric acid to zirconium dioxide being 6:1, maintain the temperature at 95°C, stir and dissolve until transparent, and obtain a crude fluorozirconic acid solution;
[0050] Step 1.2: Filter the crude fluorozirconic acid solution using a precision filter with a precision of 1 micron to obtain a fine fluorozirconic acid solution.
[0051] Step 2, synthesizing zirconium phosphate;
[0052] Step 2.1: add 60% phosphoric acid by mass into a tetrafluoro beaker, then place the tetrafluoro beaker containing phosphoric acid into an oil bath, heat to 160°C, and slowly add the fluorozirconic acid solution obtained in step 1.2, wherein the molar ratio of zirconium to phosphorus is 3:4;
[0053] Step 2.2: The solution obtained in step 2.1 is kept at 160°C for further heating reaction and evaporation. As the hydrofluoric acid generated by the reaction is continuously evaporated, a white precipitate begins to appear in the solution. The heating reaction is continued at this temperature. During the process, pure water is appropriately added to prevent the solution from being evaporated to dryness. When a large amount of precipitate is produced, the supernatant is taken and a fluoride ion meter is used for mid-control. When the hydrofluoric acid content in the supernatant is about 1.16%, the heating reaction is considered to be completed, and the supernatant is removed to obtain a precipitate.
[0054] Step 2.3 Filter the precipitate obtained in step 2.2 and wash with water until the F ion is less than 50 ppm to obtain a crude zirconium phosphate.
[0055] Step 3, drying the zirconium phosphate;
[0056] The crude zirconium phosphate obtained in step 2.3 was added to an alumina crucible and dried at 550°C for 2.5 hours. When the weight loss on ignition at 500°C was less than 0.5%, the drying was completed to obtain a zirconium phosphate product. The obtained zirconium phosphate product was tested, and the phosphorus pentoxide content was 43.6% and the zirconium oxide content was 56.2%.
[0057] Example 3
[0058] In this example, zirconium phosphate is prepared by the following steps:
[0059] Step 1, preparing a fluorozirconic acid solution;
[0060] Step 1.1: Add 45% hydrofluoric acid by mass into a tetrafluoroethylene beaker, add zirconium dioxide thereto for dissolution, the molar ratio of hydrofluoric acid to zirconium dioxide being 6:1, maintain the temperature at 100°C, stir and dissolve until transparent, and obtain a crude fluorozirconic acid solution;
[0061] Step 1.2: Filter the crude fluorozirconic acid solution using a precision filter with a precision of 1 micron to obtain a fine fluorozirconic acid solution.
[0062] Step 2, synthesizing zirconium phosphate;
[0063] Step 2.1: add 75% by mass phosphoric acid into a tetrafluoro beaker, then place the tetrafluoro beaker containing phosphoric acid into an oil bath, heat to 180°C, and slowly add the fluorozirconic acid solution obtained in step 1.2, wherein the molar ratio of zirconium to phosphorus is 3:4;
[0064] Step 2.2: The solution obtained in step 2.1 is kept at 180°C for further heating reaction and evaporation. As the hydrofluoric acid generated by the reaction is continuously evaporated, a white precipitate begins to appear in the solution. The heating reaction is continued at this temperature. During the process, high-purity water is appropriately added to prevent the solution from being evaporated to dryness. When a large amount of precipitate is produced, the supernatant is taken and a fluoride ion meter is used for mid-control. When the hydrofluoric acid content in the supernatant is about 0.37%, the heating reaction is considered to be completed, and the supernatant is removed to obtain a precipitate.
[0065] Step 2.3 Filter the precipitate obtained in step 2.2 and wash with water until the F ion is less than 50 ppm to obtain a crude zirconium phosphate.
[0066] Step 3, drying the zirconium phosphate;
[0067] The crude zirconium phosphate obtained in step 2.3 was added to an alumina crucible and dried at 600°C for 2 hours. When the weight loss on ignition at 500°C was less than 0.5%, the drying was completed to obtain a zirconium phosphate product. The obtained zirconium phosphate product was tested, and the phosphorus pentoxide content was 43.7% and the zirconium oxide content was 56.2%.
Claims
1. A method for preparing zirconium phosphate, characterized in that: The following steps are involved: Step 1, preparing a fluorozirconic acid solution; Step 1.1: adding zirconium dioxide to 40-50% hydrofluoric acid for dissolution, wherein the molar ratio of hydrofluoric acid to zirconium dioxide is 6:1, maintaining the temperature at 80-100° C., stirring and dissolving until transparent, and obtaining a crude fluorozirconic acid solution; Step 1.2: filtering the crude fluorozirconic acid solution to obtain a refined fluorozirconic acid solution; Step 2, synthesizing zirconium phosphate; Step 2.1: heating phosphoric acid with a mass fraction of 60-85% to 150-180° C., and slowly adding the fluorozirconic acid solution to the solution, wherein the molar ratio of zirconium to phosphorus is 3:4; Step 2.2: The solution obtained in step 2.1 is kept at 150-180°C for further heating reaction and evaporation. During the process, pure water / high-purity water is appropriately added to prevent it from being evaporated to dryness. When a large amount of precipitation is produced, the supernatant is taken for mid-control. When the content of hydrofluoric acid in the supernatant is less than 2%, it indicates that the heating reaction is completed, and the supernatant is removed to obtain a precipitate. Step 2.3: filtering the precipitate and washing with water until the F ion is less than 50 ppm to obtain a crude zirconium phosphate; Step 3, drying; The crude zirconium phosphate product is dried at 500-600° C. for 2-3 hours. When the weight loss on ignition at 500° C. is less than 0.5%, the drying is completed to obtain a zirconium phosphate product.
2. The method for preparing zirconium phosphate according to claim 1, characterized in that: In step 1.2, filtration is performed using a precision filter with a filtration accuracy of 1 micron.
3. The method for preparing zirconium phosphate according to claim 1, characterized in that: The mass fraction of phosphoric acid used in step 2.1 is 85%.
4. A zirconium phosphate, characterized in that The method is prepared by the method described in claim 1, 2 or 3.
5. A ceramic material, characterized in that: The zirconium phosphate according to claim 4 is added to the ceramic material.
6. A coating, characterized in that: The zirconium phosphate according to claim 4 is added to the coating.
7. A polymer composite material, characterized in that: The zirconium phosphate according to claim 4 is added to the polymer composite material.
Citation Information
Patent Citations
Method for preparing zirconium phosphate
CN1281509C